Markets, contracts, or firms? A simple model of governance - Tore Ellingsen; Topi Miettinen (Helsinki Graduate School of Economics, 2025)
We build a simple formal model of governance. Investments and control rights over assets and labor are fully contractible, but final production decisions are ex ante uncontractible, and ex post negotiations are inefficient. If sunk costs are low, suppliers own assets and trade takes the form of competitive spot market transactions. If sunk costs are large, at most one supplier is active, and governance depends on the asset's relationship-specificity. If the specificity is low, the buyer offers a "master supply agreement" to an independent supplier. If the specificity is high, the buyer owns the asset and employs the supplier.
Keywords: D23; D86; L22; 330; transaction cost; property right; relationship specificity; organization; bargaining; vertical integration; governance; inefficiency; master supply agreement; managed market